Functional genomics implicates ebony in the black pupae phenotype of tephritid fruit flies - Daniel F. Paulo; Thu N. M. Nguyen; Chris M. Ward; Renee L. Corpuz; Angela N. Kauwe; Pedro Rendon; Rocio E. Y. Ruano; Amanda A. S. Cardoso; Georgia Gouvi; Elisabeth Fung; Peter Crisp; Anzu Okada; et al. (Communications Biology)
Abstract The remarkable diversity of insect pigmentation offers a captivating avenue for studying evolution and genetics. In tephritids, understanding the molecular basis of mutant traits is also crucial for applied entomology, enabling the creation of genetic sexing strains through genome editing, thus facilitating sex-sorting before sterile insect releases. Here, we present evidence from classical and modern genetics showing that the black pupae (bp) phenotype in the GUA10 strain of Anastrepha ludens is caused by a large deletion at the ebony locus, removing the gene’s entire coding region. Targeted knockout of ebony induced analogous bp phenotypes across six major tephritid agricultural pests, demonstrating that disruption of Ebony alone is sufficient to produce the mutant trait in distantly related species. This functional characterization further allowed a deeper exploration of Ebony’s role in pigmentation and development across life stages in diverse species. Our findings offer key insights for molecular engineering of sexing strains based on the bp marker and for future evolutionary developmental biology studies in tephritids.